Metal‐Organic Framework Nanosheets as Templates to Enhance Performance in Semi‐Crystalline Organic Photovoltaic Cells. Issue 21 (22nd May 2022) - Sasitharan, Kezia; Kilbride, Rachel C.; Spooner, Emma L.K.; Clark, Jenny; Iraqi, Ahmed; Lidzey, David G.; Foster, Jonathan A.
Abstract: Optimizing the orientation, crystallinity, and domain size of components within organic photovoltaic (OPV) devices is key to maximizing their performance. Here a broadly applicable approach for enhancing the morphology of bulk heterojunction OPV devices using metal–organic nanosheets (MONs) as additives is demonstrated. It is shown that addition of porphyrin‐based MONs to devices with fully amorphous donor polymers lead to small improvements in performance attributed to increased light absorption due to nanosheets. However, devices based on semi‐crystalline polymers show remarkable improvements in power conversion efficiency (PCE), more than doubling in some cases compared to reference devices without nanosheets. In particular, this approach led to the development of PffBT4T2OD‐MON‐PCBM device with a PCE of 12.3%, which to the authors' knowledge is the highest performing fullerene based OPV device reported in literature to date. Detailed analysis of these devices shows that the presence of the nanosheets results in a higher fraction of face‐on oriented polymer crystals in the films. These results therefore demonstrate the potential of this highly tunable class of two‐dimensional nanomaterials as additives for enhancing the morphology, and therefore performance, of semi‐crystalline organic electronic devices. Abstract : Porphyrin based metal‐organic framework nanosheets are added to a range of organic photovoltaic devices resulting in the highest performing fullerene based devices reported to date. Analysis shows that for devices based on semi‐crystalline polymers, the nanosheets increase the fraction of face‐on oriented polymer crystals in the films leading to enhanced absorbance and charge transport.